La duquesa de Abrantes, una francesa entre España y Portugal - Francisco Lafarga (Cahiers de Civilisation Espagnole Contemporaine)
After providing information on the biographical aspects of the Duchess of Abrantes’ large literary output, attention is paid to her Souvenirs d’une ambassade et d’un séjour en Espagne et en Portugal, with the aim of unveiling the extent of the author’s direct knowledge of Spanish and Portuguese matters –notwishtanding the importance of bookish sources–, the voyager’s real concern about the particular situation of both countries and the parallelisms that she establishes between them.